Qu’allez-vous faire de Roméo ? - Olivier Caïra (Contextes)
Interactivity, understood as the possibility of relevant action within a diegesis, rests both on a technical device, which gives the reader‑player a grip on some fictional events, and a pragmatic aspect, the promise of offering her a choice-based experience. This power of interactive fiction is often overshadowed by the borgesian metaphor of “forking paths”, a pattern which rarely corresponds to scriptwriting practices, and by the pervasiveness of examples borrowed from computer games, which tend to naturalize interactivity as a purely digital phenomenon. By balancing, digital and analogue examples (notably from tabletop roleplaying games and storygames), this article raises five major questions about interactivity: the issue of interface with the diegesis, the type of environment which is proposed for action, the treatment of choices, the memorization or storage of events, and the interplay between script and improvisation.